Exploring college students' attitudes toward older adults: A description of methods used by the gerontological literacy network. Issue 4 (2nd October 2021) - Guest, M. Aaron; Nikzad-Terhune, Katherina; Kruger, Tina M.; Rowles, Graham D.
ABSTRACT: Recognizing the pervasiveness of negative societal attitudes toward aging and older adults is critical, as research indicates how older adults are viewed subsequently influences how they are treated. The Gerontological Literacy Network (GLN) is a multi-university collaboration established to address ingrained beliefs that underlie ageism and gerontophobia. The GLN developed a data-gathering protocol that uses drawing as a foundation to assess the gerontological literacy of college students. The protocol includes drawing what aging means, writing a paragraph describing the drawing, indicating the age at which someone is "old, " and writing words associated with "old person" and "grandma/grandpa." Results from 1, 609 protocols confirm that college students have negative views of aging as depicted in drawings of negative emotional states, illness, physical decline, and death. The presence of positive representations of aging (e.g., smiling) reveals the heterogeneity of perceptions and suggests the potential to achieve more accurate perceptions through educational interventions. This article provides an overview of the protocols and suggestions for future efforts related to gerontophobia and ageism.